Method for evaluating the binding force of a proton exchange membrane
By using a mixed solution of water and a polar organic solvent to swell the proton exchange membrane, the binding force of the proton exchange membrane can be rapidly evaluated, solving the problems of long testing cycles and complex equipment in existing technologies, and realizing a simple and low-cost binding force assessment.
Patent Information
- Application Number
- CN202611367798.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-03
- Publication Date
- 2026-11-06
AI Technical Summary
Existing methods for evaluating the binding strength of proton exchange membranes involve long testing cycles and complex equipment, making it difficult to meet the needs of rapid research and development and production testing.
The proton exchange membrane was swollen using a mixed solution containing water and a polar organic solvent, and the binding force of the proton exchange membrane was rapidly evaluated by observing or quantifying the degree of interfacial separation.
It enables rapid, simple, and low-cost evaluation of proton exchange membrane binding force, and is applicable to production process optimization and quality control.
Smart Images

Figure CN123045973A_ABST
Abstract
Description
Technical Field
[0001] This application relates to the field of hydrogen energy technology, specifically to a method for evaluating the binding force of a proton exchange membrane. Background Technology
[0002] Proton exchange membrane (PEM) electrolysis for hydrogen production has become one of the mainstream pathways for large-scale green hydrogen production due to its advantages such as compact system design, fast response speed, high hydrogen purity, and high adaptability to the volatility of renewable energy sources. As the core functional material of PEM electrolyzers, PEM membranes can be classified into homogeneous membranes and reinforced composite membranes based on their structure. However, under harsh operating conditions such as frequent start-ups and shutdowns and fluctuating power inputs, PEM electrolyzers experience mechanical stress fluctuations such as cold / heat cycling, dry / wet cycling, and differential pressure stress cycling, leading to continuous expansion and contraction. When the interlayer bonding is insufficient, especially at the interface between the reinforcing layer and the ionomer layer, delamination, blistering, and microcracks can occur, ultimately resulting in increased hydrogen permeability, a sharp decline in electrolyzer output performance, and even short-circuit failure. Therefore, rapidly and accurately evaluating the bonding strength of the PEM (e.g., interfacial bonding strength) is crucial for material selection, quality control, and process optimization.
[0003] Existing methods for evaluating the binding strength of proton exchange membranes mostly employ mechanical peeling tests, long-term wet-dry cycles, or single water immersion methods. These methods suffer from problems such as long testing cycles (several days to several weeks) and complex equipment, making it difficult to meet the needs of rapid research and development and production testing. Summary of the Invention
[0004] This application provides a method for evaluating the binding force of proton exchange membranes, aiming to solve at least some of the above-mentioned problems.
[0005] This application provides a method for evaluating the binding force of a proton exchange membrane, comprising: A proton exchange membrane and a mixed solution are provided, the mixed solution comprising water and a polar organic solvent; The proton exchange membrane was swollen using the mixed solution; The proton exchange membrane after swelling treatment was evaluated to obtain evaluation results; The binding force of the proton exchange membrane is determined based on the evaluation results.
[0006] Optionally, in some embodiments of this application, the polar organic solvent includes alcohol solvents.
[0007] Optionally, in some embodiments of this application, the alcohol solvent includes at least one of methanol, ethanol, ethylene glycol, n-propanol, and isopropanol.
[0008] Optionally, in some embodiments of this application, the volume ratio of water to polar organic solvent in the mixed solution is 8:2 to 2:8; alternatively, the volume ratio of water to polar organic solvent in the mixed solution is 6:4 to 4:6.
[0009] Optionally, in some embodiments of this application, the swelling treatment of the proton exchange membrane using the mixed solution includes: immersing the proton exchange membrane in the mixed solution.
[0010] Optionally, in some embodiments of this application, the soaking temperature of the soaking treatment is 25°C to 80°C; and / or, the soaking time of the soaking treatment is 1 min to 60 min.
[0011] Optionally, in some embodiments of this application, the swelling treatment of the proton exchange membrane using the mixed solution further includes: ultrasonic treatment of the proton exchange membrane during the soaking treatment.
[0012] Optionally, in some embodiments of this application, the evaluation method includes at least one of visual observation, optical microscopy observation, light transmittance detection, and tactile touch.
[0013] Optionally, in some embodiments of this application, the evaluation method includes visual observation, and the evaluation result includes whether the proton exchange membrane exhibits at least one of the following: interlayer separation, bubbling, white spots, wrinkles, and uneven transparency; and / or, The evaluation method includes optical microscope observation, and the evaluation results include whether the proton exchange membrane exhibits at least one of the following: microcracks, bubbles, delamination interfaces, and exposed reinforcement layers; and / or, The evaluation method includes the light transmittance test, and the evaluation result includes whether the proton exchange membrane exhibits layered areas with white haze, dark areas, or bubble shadows; and / or, The evaluation method includes the tactile touch, and the evaluation result includes whether the proton exchange membrane exhibits at least one of the following: local bulges and interlayer slippage.
[0014] Optionally, in some embodiments of this application, the proton exchange membrane is an enhanced proton exchange membrane, and determining the binding force of the proton exchange membrane based on the evaluation results is determining the interfacial binding force of the enhanced proton exchange membrane based on the evaluation results.
[0015] Optionally, in some embodiments of this application, determining the interfacial bonding force of the enhanced proton exchange membrane based on the evaluation results includes: qualitatively determining whether the enhanced proton exchange membrane exhibits delamination based on the evaluation results; determining that the interfacial bonding force of the enhanced proton exchange membrane is weak if delamination occurs; and determining that the interfacial bonding force of the enhanced proton exchange membrane is strong if no delamination occurs.
[0016] Optionally, in some embodiments of this application, determining the interfacial bonding strength of the enhanced proton exchange membrane based on the evaluation results includes: qualitatively determining the anti-delamination level of the enhanced proton exchange membrane based on the evaluation results, and determining the interfacial bonding strength level of the enhanced proton exchange membrane based on the anti-delamination level.
[0017] Optionally, in some embodiments of this application, the step of using the mixed solution to swell the proton exchange membrane; evaluating the swollen proton exchange membrane to obtain evaluation results; and determining the binding force of the proton exchange membrane based on the evaluation results includes: The enhanced proton exchange membrane was subjected to swelling treatment using mixed solutions with different volume fractions of the polar organic solvent, at a temperature of T1 and a time of t1. The enhanced proton exchange membrane after swelling treatment was evaluated to obtain the lowest volume fraction C of the polar organic solvent in the mixed solution at which the enhanced proton exchange membrane underwent stratification. min ; The enhanced proton exchange membrane was subjected to swelling treatment using a mixed solution of the polar organic solvent with a volume fraction of C1, at a temperature of T2. The enhanced proton exchange membrane after swelling treatment was evaluated to determine the shortest swelling time t during which the enhanced proton exchange membrane delamination occurred. min ; The enhanced proton exchange membrane was subjected to swelling treatment at different temperatures using a mixed solution of the polar organic solvent with a volume fraction of C2, and the swelling treatment time was t2. The enhanced proton exchange membrane after the swelling treatment was evaluated to obtain the lowest temperature T of the swelling treatment at which the enhanced proton exchange membrane delamination occurred. minn ; Based on the formula LSI=T min C min t min The LSI value is obtained by calculation.
[0018] The proton exchange membrane (PEM) binding strength evaluation method provided in this application utilizes a mixed solution containing water and a polar organic solvent to induce swelling of the PEM, rapidly stimulating swelling and shortening the evaluation cycle for rapid evaluation. Furthermore, this method eliminates the need for complex equipment, significantly reducing evaluation costs. Attached Figure Description
[0019] Figures 1-12 The images are microscopic images of the proton exchange membranes after immersion in Examples 1-12, obtained by optical microscopy at 30K magnification. Figures 13-24 These are photographs of the proton exchange membranes after soaking in Examples 1-12, respectively. Figure 25 This is a microscopic image of the proton exchange membrane after immersion in Comparative Example 1, obtained by optical microscopy at 30K magnification. Figure 26 This is a photograph of the proton exchange membrane after soaking in Comparative Example 1. Detailed Implementation
[0020] The technical solutions in the embodiments of this application will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of this application, and not all embodiments. Based on the embodiments in this application, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this application.
[0021] This application provides a method for evaluating the binding force of a proton exchange membrane. Detailed descriptions are provided below. It should be noted that the order of description of the following embodiments is not intended to limit the preferred order of the embodiments. Furthermore, in the description of this application, the term "comprising" means "including but not limited to". The terms first, second, third, etc., are used merely as illustrative and do not impose numerical requirements or establish an order. Various embodiments of the present invention may exist in the form of a range; it should be understood that the description in the form of a range is merely for convenience and brevity and should not be construed as a rigid limitation on the scope of the invention; therefore, it should be considered that the range description has specifically disclosed all possible sub-ranges and single numerical values within that range. For example, it should be considered that the range description from 1 to 6 has specifically disclosed sub-ranges, such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., and single numbers within the range, such as 1, 2, 3, 4, 5, and 6, regardless of the range. Additionally, whenever a numerical range is indicated herein, it means including any referenced number (fraction or integer) within the indicated range.
[0022] In existing technologies, commonly used methods for testing the binding force of proton exchange membranes include: (1) Mechanical peeling method: The peeling strength of the proton exchange membrane is tested by a universal testing machine to quantitatively measure the interlayer bonding force.
[0023] (2) Wet-dry cycle method: After soaking the proton exchange membrane in high temperature water (e.g., 80°C) for a period of time, it is then placed in a dry environment to dry. Repeat this cycle dozens to hundreds of times and observe whether stratification occurs.
[0024] (3) High-temperature water immersion method: Place the proton exchange membrane in deionized water at 30℃~80℃ and immerse it continuously for several days to several weeks. Take it out periodically to observe the overall condition of the proton exchange membrane.
[0025] Among these methods, mechanical peeling requires a universal testing machine, has a complex sample preparation process, and is typically performed under dry conditions, making it unable to simulate the actual delamination behavior of membranes in humid environments. While the wet-dry cycle method can simulate actual operating conditions, it has a long testing cycle and high equipment requirements, making it unsuitable for rapid screening. The high-temperature water immersion method is relatively simple to operate; however, the swelling driving force is insufficient to stimulate potential defects within the membrane, making it unable to effectively distinguish quality differences between membranes from different processes or batches.
[0026] In summary, current proton exchange membrane anti-binding strength testing technologies have long testing cycles, typically requiring several days or even weeks, which is unfavorable for R&D iterations or rapid testing in production lines. The wet-dry cycling method and the high-temperature water immersion method can only provide qualitative assessments and cannot quantitatively distinguish differences in anti-delamination performance. While the mechanical exfoliation method can provide quantitative results, sample preparation is complex, has high requirements for the membrane material itself, and the equipment is expensive. Existing methods cannot be used for rapid online evaluation.
[0027] Based on this, embodiments of this application provide a method for evaluating the binding force of a proton exchange membrane, the method comprising: Proton exchange membranes and mixed solutions are provided, the mixed solutions comprising water and polar organic solvents; The proton exchange membrane was swollen using a mixed solution; The swollen proton exchange membrane was evaluated to obtain the evaluation results; The binding force of the proton exchange membrane is determined based on the evaluation results.
[0028] Proton exchange membranes are primarily composed of perfluorosulfonic acid (PFSA) ionomers. PFSA ionomers possess a hydrophobic backbone (polytetrafluoroethylene backbone) and hydrophilic side chains (sulfonic acid groups). In pure water, the PFSA ionomer molecular chains tend to be tightly packed due to the repulsion between the hydrophobic PTFE backbone and water, while the hydrophilic sulfonic acid side chains extend outwards. The overall conformation exhibits a rigid rod-like or columnar aggregate, resulting in a non-uniform spatial distribution of the molecular chains. In pure polar organic solvents, the compatibility between the backbone and the solvent significantly increases. The original compact and ordered structure is disrupted, and the molecular chains gradually relax and undergo full solvation, transforming their conformation from a rigid rod-like state to a flexible random coil state.
[0029] When a mixed solution containing water and a polar organic solvent (water-polar organic solvent system) is used to interact with a proton exchange membrane, the polar organic solvent (e.g., alcohol) can effectively penetrate and interact with the hydrophobic backbone of the ionomer, while water mainly solvates the sulfonic acid side chains through hydrogen bonds, promoting the formation and dissociation of ion clusters. The two work synergistically to enhance the interaction energy between the ionomer and the solvent, thus making it more thermodynamically favorable for swelling behavior.
[0030] When perfluorosulfonic acid ionomers are immersed in pure water, the swelling process is relatively slow, requiring a considerable amount of time to accumulate sufficient interfacial stress. However, in a water-polar organic solvent mixture, the addition of the polar organic solvent effectively penetrates and plasticizes the hydrophobic backbone of the ionomer, enhancing its mobility. Simultaneously, water molecules promote the solvation and dissociation of the sulfonic acid side chains, and these two factors synergistically induce structural reorganization of the ionomer layer. During this process, microscopic ion clusters redistribute, macroscopically manifested as a significant expansion of the ionomer layer volume. Furthermore, the addition of the organic solvent reduces the surface tension of the system, facilitating solvent penetration into the interface between the ionomer and the reinforcing layer (such as a porous polytetrafluoroethylene support), thereby exacerbating stress concentration at the interface. Compared to the slow swelling in pure water, the mixed solvent system can induce more significant interfacial swelling stress in a shorter time, effectively accelerating the interfacial separation process between the ionomer layer and the reinforcing layer. Based on this principle, a water-polar organic solvent mixture system can be used as an accelerated evaluation medium. By observing or quantifying the degree of interfacial separation, the binding force between the ionomer and the reinforcing layer in the enhanced proton exchange membrane can be rapidly evaluated.
[0031] Let's take an enhanced proton exchange membrane (PEM) as an example. An enhanced PEM consists of an ionomer layer and a reinforcing layer. The ionomer layer is composed of perfluorosulfonic acid (PFSA) ionomers, which are highly hydrophilic and easily swell in a water-alcohol system. The reinforcing layer, on the other hand, is made of a hydrophobic or low-polarity porous material (such as polytetrafluoroethylene), which has a weak absorption capacity for polar molecules and hardly swells in a solvent system. When this enhanced PEM is placed in a water-polar organic solvent mixture, the polar organic solvent (such as alcohols) possesses both polarity and some hydrophobic properties, effectively penetrating into the ionomer layer and causing it to swell rapidly and significantly. The reinforcing layer, due to the difference in material properties, almost maintains its original size. This results in a swelling rate difference of several times or even tens of times between the ionomer layer and the reinforcing layer, inducing enormous shear stress at the interface between the two layers. When the shear stress exceeds the interfacial bonding force between the ionomer layer and the reinforcing layer, it triggers interfacial separation of the proton exchange membrane, manifesting as macroscopic defects such as delamination and blistering.
[0032] Based on the above mechanism, this method utilizes a water-polar organic solvent mixture as an accelerated evaluation medium to rapidly evaluate the bonding force between the ionomer layer and the reinforcement layer in a reinforced proton exchange membrane by applying controllable swelling stress. For reinforced proton exchange membranes prepared in different batches or under different process conditions, there are subtle differences in the interfacial bonding state between the reinforcement layer and the ionomer layer. These differences are not easily observed during a slow swelling process (such as immersion in pure water). However, under the accelerated swelling stress provided by the water-polar organic solvent mixture, areas with weaker interfacial bonding will rapidly "yield," exhibiting failure phenomena such as blistering and delamination. Therefore, by placing the reinforced proton exchange membrane under test in the mixed solvent and immersing it at a certain temperature for a predetermined time, the degree of interfacial separation of the membrane sample (such as changes in delamination area, number of bubbles, or peel strength) can be observed or quantified to quickly and intuitively evaluate the bonding force between the ionomer layer and the reinforcement layer. This method has the advantages of simple operation, short evaluation cycle, and high discrimination, and is suitable for rapid evaluation of bonding force in proton exchange membrane production process optimization and quality control.
[0033] Proton exchange membranes can be classified into homogeneous membranes and reinforced composite membranes. Homogeneous membranes are thin films made of a single material (such as Nafion perfluorosulfonic acid resin). Reinforced proton exchange membranes are composed of two or more layers of materials with different properties. The binding force of proton exchange membranes is mainly divided into two levels: interfacial binding force and cohesive force. For homogeneous membranes, the binding force mainly refers to the cohesive force, that is, the mechanical strength of the material itself within the membrane layer. For composite membranes, the binding force mainly refers to the interfacial binding force between layers, such as the binding force between the ionomer layer and the reinforcing layer.
[0034] In summary, the proton exchange membrane binding strength evaluation method provided in this application embodiment uses a mixed solution containing water and a polar organic solvent to swell the proton exchange membrane, which can quickly induce swelling of the proton exchange membrane, shorten the evaluation cycle, and achieve the purpose of rapid evaluation. Furthermore, this proton exchange membrane binding strength evaluation method does not require complex equipment, greatly reducing the evaluation cost.
[0035] In some embodiments of this application, the polar organic solvent includes alcohol solvents.
[0036] Alcohol solvents possess a hydroxyl group (-OH) in their molecular structure. This polar functional group endows alcohol molecules with polar characteristics, making them exhibit strong polarity. As an example, the mixed solution is a water-alcohol mixture (hereinafter referred to as a water-alcohol solution), which contains water and an alcohol solvent. In the water-alcohol solution, the alcohol solvent includes at least one of methanol, ethanol, ethylene glycol, n-propanol, and isopropanol.
[0037] The selection of a water-alcohol mixed solvent as the evaluation medium is based on the interaction mechanism between the unique amphiphilic molecular structure of perfluorosulfonic acid ionomers and the solvent. The main chain of perfluorosulfonic acid resin is a hydrophobic polytetrafluoroethylene backbone, with hydrophilic sulfonic acid groups at the end of the side chains. When placed in different solvents, the ionomer molecules spontaneously assemble, interacting in a way that minimizes incompatibility. In pure water, the hydrophobic fluorocarbon backbone clusters to form a core, while the hydrophilic sulfonic acid groups align outwards, forming tightly packed, elongated aggregates; the ionomer exhibits only slight swelling. In pure alcohol, the ionomer forms looser aggregates through physical cross-linking of ionic clusters.
[0038] In water-alcohol mixtures, solvent molecules can interact simultaneously with both the hydrophilic side chains and the hydrophobic backbone of Nafion, acting as a "bridge" or "medium" to effectively disrupt the original molecular self-assembly equilibrium and induce swelling of the ionomer layer. However, the degree of damage to the ionomer structure by the water-alcohol solution depends more on the matching degree of the solubility parameter (δ) between the solvent and the different components of the ionomer. Taking Nafion as an example, it has a dual solubility parameter characteristic, with the hydrophobic backbone and hydrophilic side chains matching solvents of different polarities. Pure water can only act on the hydrophilic sulfonic acid groups and cannot effectively disperse the hydrophobic fluorocarbon backbone, so the ionomer only swells slightly. When an alcohol solvent is introduced into the water, water molecules and alcohol molecules can interact with both the side chains and the backbone, thereby inducing more significant swelling of the ionomer. Meanwhile, when the alcohol content in the aqueous alcohol solution is too high, the alcohol is difficult to dissolve the main chain molecules quickly. It is necessary to rely on the interaction between water and the side chain sulfonic acid groups to open the side chain structure, which is more conducive to the further interaction between the alcohol and the main chain. This synergistic mechanism makes the swelling degree of the ionomer layer more significant.
[0039] Under the accelerated swelling stress provided by the water-alcohol mixture, areas with weak interfacial bonding will quickly "yield" and exhibit failure phenomena such as blistering and delamination, thereby enabling rapid evaluation of bonding strength.
[0040] In some embodiments of this application, the volume ratio of water to polar organic solvent in the mixed solution is 8:2 to 2:8.
[0041] Proton exchange membranes (PEMs) swell moderately in pure water, but this swelling is "uniform and controllable." When polar organic solvents, such as alcohols (especially n-propanol, a solvent with stronger swelling capacity), are added to pure water, the solubility parameters of the mixed solution change, thus affecting the swelling behavior of the PEM. The ratio of water to polar organic solvent in the mixed solution affects the solubility parameters. According to the "concentration window" effect of swelling behavior: when the concentration of polar organic solvent in the mixed solution is low (below 20 vol%), the swelling stress is weak and insufficient to trigger defects in the PEM; when the concentration of polar organic solvent in the mixed solution is within the sensitive window (usually 40 vol% to 60 vol%), the PEM enters the "rapid swelling zone," and the interlayer interface rapidly generates delamination stress due to the mismatch in swelling rates; when the concentration of polar organic solvent in the mixed solution is high (above 80 vol%), some PEMs may over-swell or dissolve, affecting the assessment.
[0042] As an example, the volume ratio of water to polar organic solvent in the mixed solution is 8:2, 7:3, 6:4, 5:5, 4:6, 3:7 or 2:8.
[0043] In some embodiments of this application, the volume ratio of water to polar organic solvent in the mixed solution is 6:4 to 4:6.
[0044] In some embodiments of this application, the volume ratio of water to polar organic solvent in the mixed solution is close to 1:1.
[0045] The concentration of the polar organic solvent in the mixed solution is 50 vol%, which is exactly within the sensitive window. When the volume ratio of water to polar organic solvent reaches about 1:1, the ionomer molecules are in a relatively relaxed equilibrium state. Under the premise of ensuring that the film is not dissolved, the "critical swelling stress" of the defects can be quickly excited, thereby rapidly amplifying and exciting the tiny difference in interlayer bonding force within a few minutes, maximizing the acceleration of swelling-induced delamination, and achieving the purpose of rapid evaluation.
[0046] In some embodiments of this application, the proton exchange membrane is swollen using a mixed solution, including immersing the proton exchange membrane in the mixed solution.
[0047] By immersing the proton exchange membrane in a mixed solution, the proton exchange membrane is rapidly permeated by the water and polar organic solvent in the mixed solution and swells quickly.
[0048] In some embodiments of this application, the immersion temperature for the soaking treatment is 25°C to 80°C. Immersion temperature refers to the temperature of the mixed solution during the immersion treatment. Appropriately increasing the immersion temperature can accelerate the penetration of the mixed solution, especially polar organic solvent molecules, and the swelling behavior of the proton exchange membrane; however, excessively high immersion temperatures may affect the stability of the membrane. As examples, immersion temperatures are 25°C, 30°C, 40°C, 50°C, 60°C, 70°C, or 80°C.
[0049] In some embodiments of this application, the soaking time for the immersion treatment is 1 min to 60 min. Extending the soaking time can allow the proton exchange membrane to swell more fully, which is beneficial for obtaining more accurate evaluation results; however, excessively long soaking times can affect the efficiency of the evaluation. As examples, the soaking times are 1 min, 10 min, 20 min, 30 min, 40 min, 50 min, or 60 min.
[0050] In some embodiments of this application, the swelling treatment of the proton exchange membrane using a mixed solution further includes: ultrasonic treatment of the proton exchange membrane during the soaking treatment.
[0051] In other words, when the proton exchange membrane is immersed in the mixed solution, it is simultaneously subjected to ultrasonic treatment. By utilizing the physical impact of ultrasound with cavitation effect as the core, combined with the synergistic effects of acoustic flow and local high temperature, channels and driving forces are created for polar organic solvent molecules, thereby efficiently promoting the swelling process of the proton exchange membrane.
[0052] In some embodiments of this application, the mixed solution can also be applied (e.g., coated) onto the surface of the proton exchange membrane, allowing it to penetrate into the membrane and swell. This method is typically suitable for online sampling scenarios. After the mixed solution is applied to the proton exchange membrane surface, hot air can be blown onto the membrane to accelerate the swelling process.
[0053] In some embodiments of this application, the evaluation methods include at least one of visual observation, optical microscopy observation, light transmittance detection, and tactile touch.
[0054] When evaluating proton exchange membranes after swelling treatment, one of the above evaluation methods can be selected individually, or multiple evaluation methods can be selected simultaneously.
[0055] As an example, after the proton exchange membrane has been swollen, the surface of the proton exchange membrane is gently rinsed with deionized water and placed under an optical microscope or directly observed to see if there are any phenomena such as delamination, bubbling, or peeling between the membrane layers.
[0056] In some embodiments of this application, the evaluation method includes visual observation. Observation is performed under natural light or a standard D65 light source at a distance of 30cm to 50cm from the swollen proton exchange membrane. When visually observing the proton exchange membrane, the evaluation results include whether the proton exchange membrane exhibits at least one of the following: interlayer separation, bubbling, white spots, wrinkles, and uneven transparency.
[0057] In some embodiments of this application, the evaluation method includes observation using an optical microscope. The proton exchange membrane's edges, surface, and interior are observed using an optical microscope at magnification of 10x to 300x to determine if at least one of the following is present: microcracks, bubbles, delamination interfaces, and exposed reinforcement layers. In other words, the evaluation results include whether the proton exchange membrane exhibits at least one of the following: microcracks, bubbles, delamination interfaces, and exposed reinforcement layers.
[0058] In some embodiments of this application, the evaluation method includes light transmittance testing. The proton exchange membrane is placed on the light stage of a light transmittance observation device, and light is passed through the proton exchange membrane to observe whether there are any abnormalities in the layered areas of the proton exchange membrane, including the presence of white fog, dark areas, or bubble shadows in the layered areas. That is, the evaluation result includes whether the proton exchange membrane shows white fog, dark areas, or bubble shadows in the layered areas.
[0059] In some embodiments of this application, the evaluation method includes tactile touch. The surface of the proton exchange membrane is gently touched with a finger to feel for any localized bulging (bubbling) or interlayer slippage. The evaluation result includes whether the proton exchange membrane exhibits at least one of localized bulging and interlayer slippage.
[0060] In some embodiments of this application, the proton exchange membrane is an enhanced proton exchange membrane, and the bonding force of the proton exchange membrane is determined based on the evaluation results.
[0061] The interfacial binding force of an enhanced proton exchange membrane (EPM) represents its anti-delamination performance. Stronger interfacial binding force results in better anti-delamination performance, while weaker interfacial binding force leads to poorer anti-delamination performance.
[0062] In some embodiments of this application, the proton exchange membrane is an enhanced proton exchange membrane. Determining the interfacial bonding force of the enhanced proton exchange membrane based on the evaluation results includes: qualitatively determining whether the enhanced proton exchange membrane has delamination based on the evaluation results; determining that the interfacial bonding force of the enhanced proton exchange membrane is weak if delamination occurs; and determining that the interfacial bonding force of the enhanced proton exchange membrane is strong if no delamination occurs.
[0063] In this context, the interfacial bonding strength of the enhanced proton exchange membrane is evaluated by assessing whether delamination occurs, thus achieving qualitative analysis.
[0064] As an example, when visual observation reveals interlayer separation in an enhanced proton exchange membrane (EPM), it is determined that the EPM has delaminated; when optical microscopy reveals a delaminated interface in the EPM, it is determined that the EPM has delaminated; when transmittance testing observes abnormal light transmission in the delaminated areas of the EPM, it is determined that the EPM has delaminated; and when a tactile sensation of interlayer slippage is felt, it is determined that the EPM has delaminated.
[0065] In some embodiments of this application, the proton exchange membrane is an enhanced proton exchange membrane. Determining the interfacial bonding force of the enhanced proton exchange membrane based on the evaluation results includes: qualitatively determining the anti-delamination level of the enhanced proton exchange membrane based on the evaluation results, and determining the interfacial bonding force level of the enhanced proton exchange membrane based on the anti-delamination level.
[0066] Generally, the higher the anti-delamination grade of an enhanced proton exchange membrane (PEM), the better its anti-delamination performance; the higher the interfacial binding strength grade, the greater its interfacial binding strength. Conversely, the lower the anti-delamination grade, the worse its anti-delamination performance; the lower the interfacial binding strength grade, the smaller its interfacial binding strength.
[0067] In this context, the interfacial binding strength of the enhanced proton exchange membrane is evaluated by its anti-stratification grade, enabling semi-quantitative analysis.
[0068] In some embodiments of this application, image processing software can be used to automatically identify the layered area, thereby achieving a more accurate semi-quantitative or quantitative evaluation.
[0069] In some embodiments of this application, the proton exchange membrane is an enhanced proton exchange membrane, and the lamination sensitivity index (LSI) is defined as: LSI = T min C min t min ; where: C min The lowest volume fraction (vol%) of polar organic solvent in the mixed solution that induces layering of an enhanced proton exchange membrane; T min The lowest temperature (in °C) at which enhanced proton exchange membrane stratification is initiated; t min The shortest time (in hours) to induce delamination of the enhanced proton exchange membrane. This can be understood as measuring C under conditions of fixed temperature and time during the swelling treatment. min T was measured under the condition that the swelling time and the concentration of the mixed solution were fixed. min ; t was measured under the conditions of constant swelling temperature and constant concentration of the mixed solution. min .
[0070] A smaller LSI value indicates that the enhanced proton exchange membrane (PEM) can delaminate in a shorter time under lower polar organic solvent concentrations and lower temperatures, meaning the enhanced MEM is more sensitive to the swelling environment and has weaker interlayer binding. By comparing the LSI values of different enhanced MEMs, the binding strength can be quantitatively ranked, enabling quantitative analysis. Specifically, the MEM is swollen using a mixed solution; the swollen MEMs are evaluated to obtain evaluation results; and the binding strength of the MEMs is determined based on the evaluation results; including: Enhanced proton exchange membranes (PEMs) were swollen using mixed solutions of polar organic solvents with different volume fractions. The swelling treatment was performed at temperature T1 and time t1. The swollen PEMs were then evaluated to determine the lowest volume fraction C of the polar organic solvent in the mixed solution at which the PEMs underwent stratification. min ; The enhanced proton exchange membrane was swollen using a mixed solution of polar organic solvent with a volume fraction of C1 at a temperature of T2. The swollen enhanced proton exchange membrane was then evaluated to determine the shortest swelling time t required for membrane delamination. min ; Enhanced proton exchange membranes were swollen at different temperatures using a mixed solution of polar organic solvent with a volume fraction of C2, with a swelling time of t2. The swollen enhanced proton exchange membranes were then evaluated to determine the lowest swelling temperature T at which stratification occurred. minn ; Based on the formula LSI=T min C min t min The LSI value is obtained by calculation.
[0071] It should be noted that T1 and T2 can be set according to specific circumstances, and T1 and T2 can be equal or unequal; t1 and t2 can be set according to specific circumstances, and t1 and t2 can be equal or unequal; C1 and C2 can be set according to specific circumstances, and C1 and C2 can be equal or unequal.
[0072] When obtaining the LSI values of different enhanced proton exchange membranes, the swelling treatment was performed using the same polar organic solvent and the same T1, t1, C1, T2, C2, and t2.
[0073] In this context, the interfacial binding force of the enhanced proton exchange membrane is evaluated by obtaining its LSI value. The smaller the LSI value, the weaker the interfacial binding force of the enhanced proton exchange membrane, thus enabling quantitative analysis.
[0074] The following description is based on specific embodiments.
[0075] Example 1 Please refer to Table 1. Using a PEEK-enhanced proton exchange membrane of model FS-990-PK, place it in a methanol-water mixed solution with a water-to-ethanol volume ratio of 5:5 (i.e., methanol concentration of 50 vol%) at room temperature (25℃±2℃) and let it stand for 5 minutes.
[0076] After soaking, remove the membrane sample, gently rinse with deionized water, and observe the surface and edge morphology of the membrane. Please refer to [link to relevant documentation]. Figure 1 and Figure 13 The results showed that the PEEK-reinforced proton exchange membrane had a smooth surface, no edge warping, and no bubbling or delamination was observed under a microscope. The surface was smooth and continuous, the reinforcing layer mesh structure was intact, and the interface bonding was tight. Please refer to Table 2. The anti-delamination level was rated as Grade V (very slight interface failure).
[0077] Example 2 Please refer to Table 1. Using a PEEK-enhanced proton exchange membrane of model FS-990-PK, place it in an ethanol-water mixed solution with a water-to-ethanol volume ratio of 5:5 (i.e., ethanol concentration of 50 vol%) at room temperature (25℃±2℃) and let it stand for 5 minutes.
[0078] After soaking, observations were made; please refer to [the relevant documentation]. Figure 2 and Figure 14 A small number of scattered protrusions appeared on the surface of the membrane sample, with slight wavy deformation at the edges, but the overall morphology remained basically intact. Under a microscope, slight dissolution of the ionomers within the grid was observed, resulting in slight delamination. Please refer to Table 2; the anti-delamination level is rated as Grade V (slight interfacial failure).
[0079] Example 3 Please refer to Table 1. Using a PEEK-enhanced proton exchange membrane of model FS-990-PK, place it in a n-propanol-water mixed solution with a water-to-alcohol volume ratio of 8:2 (i.e., n-propanol concentration of 20 vol%) and let it stand for 5 minutes at room temperature (25℃±2℃).
[0080] After soaking, observations were made; please refer to [the relevant documentation]. Figure 3 and Figure 15 In the low-concentration n-propanol system, the swelling stress was weak, the membrane sample surface was smooth, the edges were slightly warped, and there was no obvious deformation. Microscopic examination showed that the membrane surface was smooth and continuous, the PEEK reinforcement layer had a clear and complete mesh structure, no bubbling, tight interfacial bonding, and smooth edges. Please refer to Table 2, the anti-delamination level is rated as Level IV (slight interfacial failure).
[0081] Example 4 Please refer to Table 1. Using a PEEK-enhanced proton exchange membrane of model FS-990-PK, place it in a n-propanol-water mixed solution with a water-to-alcohol volume ratio of 2:8 (i.e., n-propanol concentration of 80 vol%) at room temperature (25℃±2℃) and let it stand for 5 minutes.
[0082] After soaking, observations were made; please refer to [the relevant documentation]. Figure 4 and Figure 16 Under high concentrations of n-propanol, the membrane sample was subjected to strong swelling stress, resulting in dense, fine protrusions (bubbling) on the surface, obvious edge warping, and significant membrane deformation. Microscopic examination revealed clear separation marks at the interface between the reinforcing layer and the ionomer. Please refer to Table 2; the anti-delamination level was rated as Grade III (minor interface failure).
[0083] Example 5 Please refer to Table 1. Using a PEEK-enhanced proton exchange membrane of model FS-990-PK, under constant temperature of 40℃, it was placed in a mixed solution of n-propanol and water with a water-to-alcohol volume ratio of 5:5 (n-propanol concentration 50 vol%) and allowed to stand for 5 minutes.
[0084] After soaking, observations were made; please refer to [the relevant documentation]. Figure 5 and Figure 17 Increased temperature accelerated the permeation of alcohol molecules and the swelling behavior of the membrane. After testing, small protrusions appeared on the surface of the membrane sample, with slight edge warping. Under the microscope, the protrusions of the ionomer layer were more obvious, with increased size and density. In some areas, the ionomer began to dissolve into the solvent, and local detachment occurred at the interface between the ionomer and the PEEK mesh. Please refer to Table 2. The anti-delamination level was rated as Grade II (moderate interface failure).
[0085] Example 6 Please refer to Table 1. Using a PEEK-enhanced proton exchange membrane of model FS-990-PK, place it in a n-propanol-water mixed solution with a water-to-alcohol volume ratio of 5:5 (n-propanol concentration 50 vol%) and let it stand for 5 minutes under a constant temperature of 80℃.
[0086] After soaking, observations were made; please refer to [the relevant documentation]. Figure 6 and Figure 18 High temperature conditions significantly increased swelling stress, causing the ionomer layer to separate directly from the mesh. A large amount of ionomer dissolved in n-propanol solvent, leading to breakage of the PEEK mesh and damage to the reinforcing layer structure. Please refer to Table 2; the delamination resistance level is rated as Level I (complete interface failure).
[0087] Example 7 Please refer to Table 1. Using a PEEK-enhanced proton exchange membrane of model FS-990-PK, it was placed in a n-propanol-water mixed solution with a water-to-alcohol volume ratio of 5:5 (n-propanol concentration 50 vol%) and allowed to stand for 30 minutes at room temperature (25℃±2℃).
[0088] After soaking, observations were made; please refer to [the relevant documentation]. Figure 7 and Figure 19 Extending the soaking time allows for more complete swelling, resulting in more pronounced protrusions on the membrane sample surface after soaking. The density and size of these protrusions increase, and the edges become severely warped, exacerbating membrane deformation. Under the microscope, the ionomer protrusions are more obvious, with increased size. Some ionomers have protruded beyond the PEEK mesh, causing severe deformation and distortion of the PEEK mesh structure. The separation range between the ionomers and the mesh fabric interface has expanded. Please refer to Table 2; the anti-delamination level is rated as Level II (moderate interface failure).
[0089] Example 8 Please refer to Table 1. Using a PEEK-enhanced proton exchange membrane of model FS-990-PK, it was placed in a n-propanol-water mixed solution with a water-to-alcohol volume ratio of 5:5 (n-propanol concentration 50 vol%) and allowed to stand for 60 minutes at room temperature (25℃±2℃).
[0090] After soaking, observations were made; please refer to [the relevant documentation]. Figure 8 and Figure 20 The membrane sample surface exhibited dense protrusions, with dense and interconnected bubbles, resulting in severe membrane deformation, edge curling, and in some areas, detachment of the ionomer layer from the reinforcement layer. Under the microscope, the ionomer completely dissolved from the PEEK mesh, with significant loss of ionomer within the mesh, exposing the PEEK mesh structure. Some mesh nodes showed breakage, and the ionomer-mesh interface completely separated. The reinforcement layer lost its ionomer support, resulting in a loose structure. Please refer to Table 2; the anti-delamination level is rated as Level I (severe interface failure).
[0091] Example 9 Please refer to Table 1. Using the e-PTFE enhanced proton exchange membrane with model number DM20260128002, place it in a n-propanol-water mixed solution with a water-to-alcohol volume ratio of 5:5 (n-propanol concentration 50 vol%) and let it stand for 5 minutes at room temperature (25℃±2℃).
[0092] Please refer to the observations after soaking. Figure 9 and Figure 21 The membrane sample showed good overall flatness, with delamination only clearly observed at the edges. No obvious bubbling or deformation was observed in the main membrane area. Microscopic observation revealed typical grid-like delamination at the edges (along the e-PTFE grid direction). The interface in the main area showed good adhesion with no obvious separation. Stress concentration at the edges between the e-PTFE reinforcing layer and the ionomer layer led to localized failure. Please refer to Table 2; the delamination resistance level is rated as Level IV (minor interface failure).
[0093] Example 10 Please refer to Table 1. Using Gore brand hydrogen-free proton exchange membranes, place them in a 5:5 (50 vol% n-propanol) mixed solution of n-propanol and water at room temperature (25℃±2℃) and let them stand for 5 minutes.
[0094] Please refer to the observations after soaking. Figure 10 and Figure 22 The membrane sample exhibited complete delamination, with a loose membrane structure that could be peeled off layer by layer. Microscopic observation revealed complete separation between the ionomer layer and the e-PTFE reinforcement layer, destruction of the hydrogen removal layer structure, and large-area detachment between the multilayer interfaces. Please refer to Table 2; the anti-delamination level is rated as Level I (complete interface failure).
[0095] Example 11 Please refer to Table 1. Using N115 perfluorosulfonic acid homogenized membrane (without reinforcement layer), at room temperature (25℃±2℃), it is placed in a n-propanol-water mixed solution with a water-to-alcohol volume ratio of 5:5 (n-propanol concentration 50 vol%) and left to stand for 5 minutes.
[0096] Please refer to the observations after soaking. Figure 11 and Figure 23 The homogeneous membrane has no interlayer interface. After immersion, the overall size of the membrane sample increased (uniform swelling), with only ionomer dissolution appearing on the surface. Microscopic observation revealed that the membrane swelled uniformly, with no interfacial separation. Fine pores left by the partial dissolution of ionomers were visible on the surface. The overall structure remained intact, with no heterogeneous interface failure. Please refer to Table 2. The anti-delamination level is rated as Grade V (no delamination, but swelling and dissolution occurred).
[0097] Example 12 Please refer to Table 1. Using a PEEK-enhanced proton exchange membrane of model FS-990-PK, place it in a n-propanol-water mixed solution with a water-to-alcohol volume ratio of 5:5 (i.e., n-propanol concentration of 50 vol%) at room temperature (25℃±2℃) and let it stand for 5 minutes.
[0098] After soaking, remove the sample, gently rinse with deionized water, and observe the surface and edge morphology of the membrane. Please refer to [link / reference]. Figure 12 and Figure 24 The results showed dense, fine bumps (bubbling) on the surface of the membrane sample, with obvious edge warping and significant membrane deformation. Microscopic examination revealed slight protrusions in the ionomer layer, distributed as isolated dots. The PEEK mesh structure remained largely intact, and the interface between the ionomer and the mesh remained in contact. However, signs of separation were observed at the interface between the reinforcing layer and the ionomer. Please refer to Table 2 for the anti-delamination rating: Level III (slight interface failure).
[0099] Comparative Example 1 Please refer to Table 1. Using a PEEK-enhanced proton exchange membrane of model FS-990-PK, place it in ultrapure water and let it stand for 5 minutes at room temperature (25℃±2℃).
[0100] After soaking, remove the sample, gently rinse with deionized water, and observe the surface and edge morphology of the membrane. Please refer to [link / reference]. Figure 25 and Figure 26 The results showed that the membrane sample surface was smooth and flat, without any protrusions or bubbles, with complete and straight edges. The membrane did not undergo any deformation, and its appearance was completely consistent with the unimmersed sample. Under the microscope, the PEEK mesh structure was found to be complete and clear, without distortion or breakage. The ionomer layer was uniformly covered on the PEEK mesh, without any protrusions or dissolution. The ionomer and PEEK mesh interface were tightly bonded, with no signs of separation or ionomer dissolution. Please refer to Table 2 for the anti-delamination rating: Grade V (no delamination).
[0101] Table 1
[0102] Table 2
[0103] It can be seen that the proton exchange membrane binding force evaluation method provided in this application has the following advantages: (1) Fast testing speed: Simultaneously control the type of alcohol, alcohol concentration, soaking temperature and time to construct environments with different polarities and swelling intensities, and quickly stimulate the stratification behavior. The stratification behavior of the proton exchange membrane can be stimulated in as little as a few minutes (e.g., 5-10 minutes). Compared with the traditional method of several days to several weeks, the testing time is significantly shortened and the efficiency is improved by nearly 100 times.
[0104] (2) Easy to operate: No complicated equipment is required. Evaluation can be completed with just a constant temperature water bath, container and microscope or visual inspection. It is low cost and suitable for rapid testing in laboratories and production lines.
[0105] (3) High sensitivity: By adjusting the type and concentration of alcohol, different degrees of swelling stress loading can be achieved for different membrane materials (reinforced membrane, homogeneous membrane), effectively distinguishing the differences in anti-delamination performance.
[0106] (4) Qualitative, semi-quantitative and quantitative evaluation: Based on the stratification phenomenon, rapid classification is carried out, which is applicable to the comparative screening of different membrane materials, including reinforced membranes and homogeneous membranes. It has good versatility and makes up for the shortcomings of existing qualitative methods.
[0107] In summary, this application provides a method for evaluating the binding force of proton exchange membranes. This method is a test method for rapidly evaluating the anti-stratification performance of proton exchange membranes by adjusting parameters. It aims to construct environments with different polarities and swelling intensities by systematically adjusting four parameters: alcohol type, alcohol concentration, soaking time, and soaking temperature. This rapidly induces the stratification behavior of proton exchange membranes (including reinforced membranes and homogenized membranes), and achieves qualitative, semi-quantitative, or quantitative evaluation of the binding force between membrane layers through direct observation.
[0108] The above provides a detailed description of a method for evaluating the binding force of a proton exchange membrane according to embodiments of this application. Specific examples have been used to illustrate the principles and implementation methods of this application. The descriptions of the above embodiments are only for the purpose of helping to understand the method and core ideas of this application. At the same time, for those skilled in the art, there will be changes in the specific implementation methods and application scope based on the ideas of this application. Therefore, the content of this specification should not be construed as a limitation of this application.
Claims
1. A method for evaluating the binding force of a proton exchange membrane, characterized in that, include: A proton exchange membrane and a mixed solution are provided, the mixed solution comprising water and a polar organic solvent; The proton exchange membrane was swollen using the mixed solution; The proton exchange membrane after swelling treatment was evaluated to obtain evaluation results; The binding force of the proton exchange membrane is determined based on the evaluation results.
2. The method for evaluating the binding force of a proton exchange membrane according to claim 1, characterized in that, The polar organic solvents include alcohol solvents.
3. The method for evaluating the binding force of a proton exchange membrane according to claim 2, characterized in that, The alcohol solvent includes at least one of methanol, ethanol, ethylene glycol, n-propanol, and isopropanol.
4. The method for evaluating the binding force of a proton exchange membrane according to any one of claims 1 to 3, characterized in that, The volume ratio of water to polar organic solvent in the mixed solution is 8:2 to 2:8; optionally, the volume ratio of water to polar organic solvent in the mixed solution is 6:4 to 4:
6.
5. The method for evaluating the binding force of a proton exchange membrane according to any one of claims 1 to 3, characterized in that, The swelling treatment of the proton exchange membrane using the mixed solution includes: immersing the proton exchange membrane in the mixed solution.
6. The method for evaluating the binding force of a proton exchange membrane according to claim 5, characterized in that, The soaking temperature for the soaking treatment is 25℃~80℃; and / or, The soaking time for the soaking treatment is 1 min to 60 min; and / or, The method of using the mixed solution to swell the proton exchange membrane further includes: ultrasonic treatment of the proton exchange membrane during the soaking treatment.
7. The method for evaluating the binding force of a proton exchange membrane according to any one of claims 1 to 3, characterized in that, The evaluation methods include at least one of the following: visual observation, optical microscopy observation, light transmittance detection, and tactile touch.
8. The method for evaluating the binding force of a proton exchange membrane according to claim 7, characterized in that, The evaluation method includes visual observation, and the evaluation results include whether the proton exchange membrane exhibits at least one of the following: interlayer separation, bubbling, white spots, wrinkles, and uneven transparency; and / or, The evaluation method includes optical microscope observation, and the evaluation results include whether the proton exchange membrane exhibits at least one of the following: microcracks, bubbles, delamination interfaces, and exposed reinforcement layers; and / or, The evaluation method includes the light transmittance test, and the evaluation result includes whether the proton exchange membrane exhibits layered areas with white haze, dark areas, or bubble shadows; and / or, The evaluation method includes the tactile touch, and the evaluation result includes whether the proton exchange membrane exhibits at least one of the following: local bulges and interlayer slippage.
9. The method for evaluating the binding force of a proton exchange membrane according to any one of claims 1 to 3, characterized in that, The proton exchange membrane is an enhanced proton exchange membrane, and the determination of the binding force of the proton exchange membrane based on the evaluation results is the determination of the interfacial binding force of the enhanced proton exchange membrane based on the evaluation results.
10. The method for evaluating the binding force of a proton exchange membrane according to claim 9, characterized in that, Determining the interfacial bonding strength of the enhanced proton exchange membrane based on the evaluation results includes: qualitatively determining whether the enhanced proton exchange membrane exhibits delamination based on the evaluation results; determining that the interfacial bonding strength of the enhanced proton exchange membrane is weak if delamination occurs; and determining that the interfacial bonding strength of the enhanced proton exchange membrane is strong if no delamination occurs. Alternatively, Determining the interfacial bonding strength of the enhanced proton exchange membrane based on the evaluation results includes: qualitatively determining the anti-delamination level of the enhanced proton exchange membrane based on the evaluation results, and determining the interfacial bonding strength level of the enhanced proton exchange membrane based on the anti-delamination level; or The process of swelling the proton exchange membrane using the mixed solution, evaluating the swollen proton exchange membrane to obtain evaluation results, and determining the binding force of the proton exchange membrane based on the evaluation results includes: The enhanced proton exchange membrane was subjected to swelling treatment using mixed solutions with different volume fractions of the polar organic solvent, at a temperature of T1 and a time of t1. The enhanced proton exchange membrane after swelling treatment was evaluated to obtain the lowest volume fraction C of the polar organic solvent in the mixed solution at which the enhanced proton exchange membrane underwent stratification. min ; The enhanced proton exchange membrane was subjected to swelling treatment using a mixed solution of the polar organic solvent with a volume fraction of C1, at a temperature of T2. The enhanced proton exchange membrane after swelling treatment was evaluated to determine the shortest swelling time t during which the enhanced proton exchange membrane delamination occurred. min ; The enhanced proton exchange membrane was subjected to swelling treatment at different temperatures using a mixed solution of the polar organic solvent with a volume fraction of C2, and the swelling treatment time was t2. The enhanced proton exchange membrane after the swelling treatment was evaluated to obtain the lowest temperature T of the swelling treatment at which the enhanced proton exchange membrane delamination occurred. minn ; Based on the formula LSI=T min C min t min The LSI value is obtained by calculation.
